PREPARATION OF 2-AMINOETHYLSULFONIC ACID - Widiyarti, Galuh; Hanafi, Muhammad; Isnijah, Siti; Kardono, Broto Sugeng; Ermawan, Ermawan; Ngadiman, Ngadiman; Sundowo, Andini (Makara Journal of Science, 2009)
Preparation process of 2-aminoethylsulfonic acid (taurine) from ethanolamine, sulfuric acid and sodium sulfite has been studied. The process involves two steps of reactions, the first was esterification of ethanolamine (H2N-CH2-CH2-OH) with sulfuric acid to produce the intermediate product of 2-aminoethyl ester (H2N-CH2-CH2-OSO3H) which then was extended to the second step by sulfonation with sodium sulfite to produce 2-aminoethylsulfonic acid (H2N-CH2-CH2- SO3H). These two process conditions were observed by varying mole ratio of reactants, temperature and time period of reactions. Taurine product was qualitatively analyzed using 1 H-NMR and LC-MS. Physical-chemical analysis were done by observing its melting point and determining its water, chloride and sulfate contents. Its melting point, water content, and sulfate content were 290o C, 0.303%, and 3 ppm, respectively, while its chloride content was undetected. After purification, the yield of process was 25.57%.